2009
DOI: 10.1111/j.1526-4637.2009.00615.x
|View full text |Cite
|
Sign up to set email alerts
|

N-of-1 Randomized Trials to Assess the Efficacy of Gabapentin for Chronic Neuropathic Pain

Abstract: The response rate and mean reduction in symptoms with gabapentin were small. Gabapentin prescribing posttrial was significantly influenced by the trial results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 16 publications
1
45
0
Order By: Relevance
“…These results have been described in detail elsewhere and are summarized in Table 2. [8][9][10]16 The rates of persistence with the treatment decision from the trial at 12 months were greatest for ADHD participants at approximately 70%, followed by 45% for celecoxib participants, and 32% of the participants from the neuropathic pain trial. The persistence rate in the celecoxib trial may have been reduced by well-publicized warnings published in the media and understandable anxiety.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results have been described in detail elsewhere and are summarized in Table 2. [8][9][10]16 The rates of persistence with the treatment decision from the trial at 12 months were greatest for ADHD participants at approximately 70%, followed by 45% for celecoxib participants, and 32% of the participants from the neuropathic pain trial. The persistence rate in the celecoxib trial may have been reduced by well-publicized warnings published in the media and understandable anxiety.…”
Section: Resultsmentioning
confidence: 99%
“…9,10,16,17 In addition, persistence was high for the ADHD trial (70%). Indeed, another methylphenidate N-of-1 study has shown >80% persistence with the joint decision at similar time periods.…”
Section: Discussionmentioning
confidence: 99%
“…Gabapentinoids benefit neuropathic cancer pain but may also reduce visceral and bone pain. Several studies involving treatment of neuropathic cancer pain found gabapentin to be the most commonly prescribed adjuvant [24, [66][67][68][69][70][71]. Gabapentin is also effective in a multitude of other symptoms including insomnia [72][73][74], cough [75][76][77], hiccough [78][79][80], nausea [81][82][83], and delirium [84].…”
Section: Discussionmentioning
confidence: 99%
“…people with arthritic pain comparing celecoxib with long-acting paracetamol [17], chronic neuropathic pain treated with gabapentin [18], pediatric oncology [19], and in pediatric rheumatology [20]. Aggregated n-of-1 studies builds on the individual (n-of-1) trial design and crossover trial designs, the details of which have also been described elsewhere (including types of conditions, interventions, measures, and implementation) [6e8,11].…”
Section: What Is New?mentioning
confidence: 99%